The Study of Structural- Mechanical and Physicochemical Properties of the Drug Antimicrobial and Anesthetic Action - Viktoria Tarasenko (Journal of Global Pharma Technology, 2020)
Introduction: This work is devoted to study of structural-mechanical and physicochemical properties of soft drugs with antimicrobial and anesthetic action. The purpose of this study was to study the effectiveness of physicochemical properties of soft drugs. Materials and methods: In the process of performing the work, pharmaco-technological, physicochemical, structural-mechanical, biopharmaceutical and biological research methods according to the State Pharmacopoeia of Ukraine were used. Results and discussion: The sample was considered stable if no stratification was observed in the tubes after centrifugation. If at least one of the tubes was observed stratification of the sample or the selection of sediment, the analysis was repeated with new portions. The type of emulsions was determined by dilution and staining methods. The study of local anesthetic activity was performed on a model of rabbit eye anesthesia. The experiment was performed on 25 male rabbits, which were divided into 5 groups of 5 rabbits each. Conclusions: The study of structural-mechanical and physico-chemical properties of drugs in the form of a cream is the basis for improving its therapeutic efficacy, mechanical stability and consumer properties. Keywords: Soft drugs, Antimicrobial action, Anesthetic action, Colloidal stability, Thermal stability, Emulsions, Rheogram.